End of 2022/23 season influenza vaccine effectiveness in primary care in Great Britain - Whitaker, HJ; Willam, N; Cottrell, S; Goudie, R; Andrews, N; Evans, J; Moore, C; Agrawal, U; Hassell, K; Gunson, R; Zitha, J; Anand, S; et al. (Wiley, 2024)
Background The 2022/23 influenza season in the United Kingdom saw the return of influenza to prepandemic levels following two seasons with low influenza activity. The early season was dominated by A(H3N2), with cocirculation of A(H1N1), reaching a peak late December 2022, while influenza B circulated at low levels during the latter part of the season. From September to March 2022/23, influenza vaccines were offered, free of charge, to all aged 2–13 (and 14–15 in Scotland and Wales), adults up to 49 years of age with clinical risk conditions and adults aged 50 and above across the mainland United Kingdom. Methods End-of-season adjusted vaccine effectiveness (VE) estimates against sentinel primary-care attendance for influenza-like illness, where influenza infection was laboratory confirmed, were calculated using the test negative design, adjusting for potential confounders. Methods Results In the mainland United Kingdom, end-of-season VE against all laboratory-confirmed influenza for all those > 65 years of age, most of whom received adjuvanted quadrivalent vaccines, was 30% (95% CI: −6% to 54%). VE for those aged 18–64, who largely received cell-based vaccines, was 47% (95% CI: 37%–56%). Overall VE for 2–17 year olds, predominantly receiving live attenuated vaccines, was 66% (95% CI: 53%–76%). Conclusion The paper provides evidence of moderate influenza VE in 2022/23.